Surface energetics of wurtzite and sphalerite polymorphs of zinc sulfide and implications for their formation in nature. (1st January 2023) - Subramani, Tamilarasan; Lilova, Kristina; Householder, Megan; Yang, Shuhao; Lyons, James; Navrotsky, Alexandra
Abstract: Surface energetics of zinc sulfide nanoparticles determines their structure, properties, and occurrence. Using a combination of experimental techniques, we investigated the thermodynamics of the two polymorphs, sphalerite and wurtzite at bulk and nanoscale to understand their occurrence. Calorimetric measurements confirmed that wurtzite has a lower surface energy than sphalerite, which causes a reversal in phase stability at the nanoscale, with wurtzite energetically stable for particle size below 10 nm. Taking these surface energies into account, a simple model of the thermodynamics of the sphalerite - wurtzite transformation as a function of particle size and temperature can explain the occurrence of the zinc sulfide polymorphs in environments as diverse as ore bodies and planetary atmospheres.